Membangun Karakter Bermisi: Menyelaraskan Kurikulum Merdeka Dengan Teologi Misi Kristen - Rajiman Andrianus Sirait; Maria Titik Windarti (LPPM - STT Kadesi Bogor, 2024)
The importance of Christian learning and formation became very significant, especially in the era of an independent curriculum that emphasized character development as the core of education. This process is more than just moral and intellectual formation, but it is a step towards transformation into a